Analisis Program Pemberdayaan Ekonomi Mustahik Melalui Zakat Produktif Oleh Baznas Kabupaten Probolinggo - Waqiatul Aqidah (Journal of Law, Economics, and Engineering, 2026)
This study aims to analyze the efforts of economic empowerment mustahik through productive zakat program BAZNAS. The locus of this research is in BAZNAS, Probolinggo Regency, and the focus of this research is productive zakat program. The subjects of this study were the beneficiaries of business funds. This study uses data collection techniques in the form of observation, interviews, and documents. Data analysis techniques include data collection, data condensation, data presentation, and conclusion. The result of this research is that the implementation process of zakat program has been in accordance with the regulations set BAZNAS and right on target. The business funding assistance Program has a positive impact on mustahik micro enterprises, including helping mustahik in the procurement of business capital and work tools, developing business capacity, changes in income, and helping mustahik in maintaining its business with the capital turnover provided. However, this empowerment program also faces several obstacles, including the lack of supervision of Business Fund Management, low transparency, lack of business assistance, and there has been no collaboration with other agencies in its implementation. Thus, there is a need for active and periodic monitoring and evaluation to monitor the development of essential businesses, regular business assistance, and program collaboration with other institutions that can support the implementation of this empowerment. Keyword: Economic Empowerment, Mustahik, Productive Zakat